Original in: Album 141. Text on back of original: "A mon vaillant frère d' armes et ami Domela Nieuwenhuis, Paris, 25 mai 92"
Original in: Album 141. Text on back of original: "A mon vaillant frère d' armes et ami Domela Nieuwenhuis, Paris, 25 mai 92".